The Influence of Organizational Environment and Intrinsic Motivation on The Attachment of GenBI Cirebon Members - Putri, Angelina Adinda; Nur'annisa, Maharani Salsabila; Kartono, Kartono; Wibowo, Sandi Nasrudin (Rescollacom (Research Collaborations Community), 2025)
Member attachment plays an important role for individuals in the Generasi Baru Indonesia (GenBI) Cirebon community, because it is directly related to active participation and scholarship sustainability. This study was conducted to determine the magnitude of the impact of the organizational environment on attachment and intrinsic motivation on attachment. This study used quantitative methods and collected data from a sample of 75 members using a survey questionnaire. This study used SPSS to manage and analyze the data. The findings of this study indicate that the effect of organizational environment on attachment has a significant positive effect, the effect of intrinsic motivation on attachment has a significant positive effect on attachment. Therefore, this study confirms that the importance of organizational environment factors as well as intrinsic motivation in increasing member engagement. This shows that organizational environmental factors and intrinsic motivation play a significant role in shaping the attachment of GenBI Cirebon members.